Teleportation in Virtual Reality; A Mini-Review - Prithul, Aniruddha; Adhanom, Isayas Berhe; Folmer, Eelke (Frontiers in Virtual Reality, 2021)
Teleportation is a popular and widely implemented virtual locomotion technique that allows users to navigate beyond the confines of available tracking space with a low possibility of inducing Virtual Reality (VR) sickness. This paper provides a comprehensive overview of the current state of research on teleportation. We report results from user studies that have evaluated teleportation in comparison to other locomotion techniques. In addition, we survey improved versions of teleportation and identify a number of areas for future research.